Metallic alloy with shape memory – selected properties and engineering aspects - Kuś, Krzysztof; Frączyk, Adam; Wojtkowiak, Adam (Technical Sciences, 2019)
In the case of shape memory alloys (SMA), a form to which a material is expected to return during heating can be repeatedly programmed, whereas other related properties can be individually adjusted. It was found that most producers of commercial assortment based on SMA as well as traders are seldom willing to lift the veil of secrecy on this topic. In the context of own experimental studies, the authors made a reference to the technical aspects of some post-treatments of a Ni-Ti alloy with a view to further practical application, e.g. the design and construction of machinery and structures with the involvement of SMA. For these purposes, high-temperature shape setting trials were carried out using various parameters of heat treatment with no secrecy surrounding the procedures applied. Some of the tested parameters proved effective, whereas some were less useful. Following the activation of the reverse transformation by heating, a somewhat different behaviour was observed, and simultaneously one of the crucial material temperatures was determined. The paper as a whole is reported from a specifically engineering/technical point of view, which is continuously emphasized in the content of the presented article.